(Invited) Effects of Microstructure on Surface Segregation: Role of Grain Boundaries. (26th April 2016) - Téllez, Helena; Druce, John; Ishihara, Tatsumi; Kilner, John A.
Abstract : The effects of microstructure on the kinetics of strontium segregation in La0.6 Sr0.4 CoO3-δ ceramic samples are investigated. A faster segregation of the Sr cations towards the surface was observed after annealing for 1 h at 600 °C in dry oxygen (pO2 = 200 mbar) as the density of grain boundaries at the surface increases ( i.e. with a decrease of the grain size). The presence of surface impurities, such as Na, partially inhibits the Sr segregation towards the surface. Optical micrographs and ToF-SIMS chemical imaging showed that the segregation and precipitation of Sr starts at the grain boundaries, with an apparent enrichment of the surface around the grain boundary via Sr surface diffusion.